Extraction, Utilization Pattern and Prioritization of Fuel Resources for Conservation in Hydro-electric Power Project Areas in Kullu District, Himachal Pradesh, Northwestern Himalaya - Sharma, Pankaj; Samant, S. S. (Indian Forester, 2021)
In hilly areas, fuelwood is the major source of the energy and it provides almost all of the cooking energy requirements. There are millions of people living inside the protected and unprotected areas with dependencies on these areas for essential services. Among these, fuelwood and fodder are two important and critical components of the village economy especially in the hills and the annual wood consumption is very high. Information on fuelwood resources, their extraction and availability are very scanty. Therefore, the present study was carried out to study the diversity of fuelwood species, annual collection, preference, and availability of fuel species in the forests. Forty six species (33 Trees and 13 Shrubs) were extracted for fuel by the inhabitants. Species preference ranged from 0.05-0.55 Probability Use (PU) and was highest for Cedrus deodara (0.55), followed by Picea smithiana, Pinus wallichiana and Quercus leucotrichophora (0.50, each), Alnus nitida, Quercus floribunda and Ulmus wallichiana (0.45, each) and Ulmus villosa (0.40). Use pressure ranged from 1.35-826.65 Resource Use Index (RUI and was highest for Cedrus deodara (826.65), followed by Picea smithiana (675.00), Quercus leucotrichophora (630.00), Pinus wallichiana (558.00) and Quercus floribunda (348.30). Therefore, immediate actions are suggested to sustain the current and future demand for fuelwood. Awareness among the villagers and mass multiplication through conventional and in-vitro methods for the species facing high anthropogenic pressures and their establishment and maintenance in the in-situ and ex-situ conditions may help in the conservation and management of these species.